Трипс гладіолусовий (Thysanoptera, Terebrantia) та заходи управління його чисельністю - Chumak, P.Ya. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The data about damage of gladiolus sorts to Thrips simplex Morison are given. The ecologically safe method of plant protection from this pest is described.